Lab-scale optimisation of Kefir beverage production from mass-cultured and freeze-dried kefir grains - Latsky, Anneline (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2004.